The Application of Augmented Reality for Improving Basketball Shooting Skills: A Systematic Literature Review - I Putu Agus Dharma Hita (Goodwood Publishing, 2026)
Purpose: This study aims to examine how augmented reality contributes to the improvement of basketball shooting skills and to build a conceptual synthesis of the cognitive, affective, and psychomotor mechanisms that explain this contribution. Research Methodology: A systematic literature review was conducted by identifying, screening, and analyzing scholarly articles published between 2020 and 2026 that addressed augmented reality, interactive digital media, and technology assisted training in basketball and related sports. Content analysis was applied to identify recurring patterns, agreements, and divergences among the reviewed studies. Results: The synthesis shows that augmented reality strengthens conceptual understanding of shooting mechanics, increases learner motivation and active participation, and improves shooting accuracy and motor coordination through three dimensional visualization and real time feedback. Conclusions: Augmented reality functions as a pedagogical bridge between technical demonstration and authentic practice, offering a promising avenue for modernizing shooting instruction in physical education. Limitations: The review relies on secondary literature rather than original experimental data, and the number of studies focusing specifically on basketball shooting remains limited. Contributions: This study offers an integrative conceptual framework linking augmented reality features to cognitive, affective, and psychomotor outcomes, providing a theoretical foundation for future empirical research and practical implementation in physical education curricula.